METAL PRECIPITATION OF FE, MN, AND AL FROM ACID MINE DRAINAGE USING ELECTROCHEMICAL NEUTRALIZATION METHOD - Puspita Rani, Stella
Opening a mining site will devastate environment because the sulfide minerals in mining location can get oxidized into acid mine drainage. Acid mine drainage has low pH that dissolve heavy metal and cause water and soil pollution. To avoid those losses, electrochemical neutralization is chosen as one of the active methods in acid mine drainage treatment. This treatment method will neutralize acid and precipitate metal through electrolysis. This method is economical because there is no continuous adding of chemicals and does not need sacrificial anode. Electricity as the main energy source has the potential to be substituted for renewable energy. This study will examine the characteristic curves, the effect of experimental variations through operating power in acid mine water recovery through electrochemical neutralization. The purpose of this research is optimizing the performance of electrochemical cell series in the electrochemical neutralization process of acid mine water through MATLAB simulation. To create and validate electrolysis I-V curve modeling, determine the effect of variations in operating temperature, type of cathode material, and anolyte concentration on the I-V curve, determine the significance and interaction of experimental variations, and estimate the metal recovery are the objectives. The main experiments consist of making, validating, adjusting the I-V curve model, simulating and analyzing the process variations, and estimating metal recovery. Simulations were carried out in two compartments with Na2SO4 as anolyte and acid mine drainage as catholyte, 500 mL each compartment and separated by Nafion N117 with IrO2 plate anode. Operating temperature variation from 30-80oC increases cell performance with diminished overpotential. The decrease in cell performance is resulted from cathode material variation, respectively platinum, nickel, stainless steel, graphite, and copper plates. The anolyte concentration 0,01-0,15 M had no effect on the I-V curve. The variation in operating temperature and the type of cathode material had a significant effect with p-values of 3,58 x 10-5 and 2,61 x 10-26, respectively. The metal recovery process was carried out at a current density of 24,75 mA/cm2, operating temperature 80oC, nickel cathode by producing Fe(OH)3, Al(OH)3, and MnO2 slurry until pH i7 is reached.